2014
DOI: 10.1080/17450101.2013.874836
|View full text |Cite
|
Sign up to set email alerts
|

Everyday Life Mobilities of Older Persons – A Case Study of Ageing in a Suburban Landscape in Sweden

Abstract: This paper describes the changing everyday life mobility of an older couple living in a suburb in Sweden. The methods used are longitudinal interviews and timegeographical diaries. The results show a pronounced dependence on car use. Representations of suburbia -as places of freedom, independence and mobility enabled by private carsdevolve into a harsh reality, i.e. disabling lock-in effects for people gradually losing locomotion, and experiencing diminishing mobility capital and social intercourse. From a tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 42 publications
0
31
0
1
Order By: Relevance
“…Second, the very ability to process information, understanding its contents and putting it into use, may change according to different cognitive and literacy skills. The ability to make use of information is a dynamic skill, which could be acquired, adapted or lost over one's life (Banister & Bowling, 2004;Goodman et al, 2014;Stjernborg, Wretstrand, & Tesfahuney, 2014), and the loss of such ability is a problem especially for ageing populations (Nordbakke, 2013;Ryan et al, 2015). A partial response in this sense are the employment of universal design in apps and the development of devoted apps for people with disabilities (Gebresselassie & Sanchez, 2018).…”
Section: Varied Forms Of Informationmentioning
confidence: 99%
“…Second, the very ability to process information, understanding its contents and putting it into use, may change according to different cognitive and literacy skills. The ability to make use of information is a dynamic skill, which could be acquired, adapted or lost over one's life (Banister & Bowling, 2004;Goodman et al, 2014;Stjernborg, Wretstrand, & Tesfahuney, 2014), and the loss of such ability is a problem especially for ageing populations (Nordbakke, 2013;Ryan et al, 2015). A partial response in this sense are the employment of universal design in apps and the development of devoted apps for people with disabilities (Gebresselassie & Sanchez, 2018).…”
Section: Varied Forms Of Informationmentioning
confidence: 99%
“…A particularly privileged site of observation are those “places of in‐between‐ness” or “transfer points” (Kesselring, ), such as airport terminals. Time–space diaries are a further means to record respondents' mobility and their different enactments in different locations over a certain period (Stjernborg, Wretstrand, & Tesfahuney, ). Moving beyond physical mobilities, imaginative and virtual mobilities can be studied by using online resources and multimedia methods (Sheller & Urry, ).…”
Section: The New Mobilities Paradigm: What Place For Older Migrants?mentioning
confidence: 99%
“…When older people have been considered it is as "left-behind" kin and their relationships with more mobile younger relatives (Reynolds, 2011;Vathi & King, 2011). However, in recent years, a new interest in older people's mobilities has emerged, focusing particularly on the role of mobility in facilitating well-being in later life (Nordbakke & Schwanen, 2014;Stjernborg et al, 2015).…”
Section: The New Mobilities Paradigm: What Place For Older Migrants?mentioning
confidence: 99%
“…Older people's mobility and travel activities have received little attention in studies using a timegeographical perspective. Stjernborg et al (2015) is one exception. They explored the mobility of an older couple through interviews and travel diaries and found that time-demanding basic needs and limited access to modes of transport due to deteriorating health and location of residence implied capability constraints.…”
Section: Meanings and Experiences Of Travelling In Time And Spacementioning
confidence: 99%